Implementasi Interaksi Sosial dan Kearifan Lokal dalam Konservasi Lingkungan Kampung Sasirangan Banjarmasin - Melly Agustina Permatasari; Yuni Suprapto; Deka Setiawan; Dewi Liesnoor Setyowati (Universitas Gadjah Mada, 2021)
Local wisdom has been associated with environmental conservation. How local wisdom and social practice shape determine environmental conservation is apparent in the the communities living along the rivers in Banjarmasin Sasirangan. Based on a qualitative approach with case studies of Sasirangan craftsmen. In Sasirangan Village, Banjarmasin City, this study aims to analyses the correlation between social interaction, local wisdom, and environmental conservation Sasirangan. The informants are craftsmen and Sasirangan traders. The data was collected through observation, interviews with craftsmen and Sasirangan traders, as well as documents study. This study concludes that the social interactions occur between craftsmen and craftsmen, craftsmen and groups of craftsmen, and between groups of craftsmen by collaborating in making Sasirangan products and competition in determining the color, motif and Sasirangan marketing. In this process, local culture plays a key role in the form of Sasirangan cloth which has various colors and motifs with certain meanings which are continuously produced, preserved and passed down from generation to generation This creates a mechanis of social interaction and local wisdom that promotes environmental conservation through the cooperation between craftsmen in the manufacture of Sasirangan products using natural colors from nature that are environmentally friendly. By not using chemical coloring, the practice reduces the pollution of river environment in Sasirangan Village, Banjarmasin.